2020
DOI: 10.14814/phy2.14550
|View full text |Cite
|
Sign up to set email alerts
|

Oral contraceptives and menstrual cycle influence autonomic reflex function

Abstract: Progesterone and its analogues are known to influence ventilation. Therefore, the purpose of this study was to investigate the role of endogenous and pharmaceutical female sex hormones in ventilatory control during the activation of the metaboreflex, mechanoreflex, and CO2 chemoreflex. Women aged 18–30 taking (n = 14) or not taking (n = 12) oral contraceptives (OC and NOC, respectively) were tested in the low hormone (LH) and high hormone (HH) conditions corresponding to the early follicular and mid‐luteal pha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
11
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 14 publications
(30 citation statements)
references
References 65 publications
2
11
0
Order By: Relevance
“… 1 28 With resuming exogenous hormone consumption, a stable hormone profile emerges; the inhibitory effects of both the oestrogen and the progestin components are established through synergistic interactions at the hypothalamic–pituitary level. Recently, Assadpour et al 29 suggested the chronic upregulation of β-adrenergic receptors of BC users may play a role in the upregulation of ventilatory rate, and autonomic reflex function, which is reflected in the patterning of the women on BC of this study of decreased HRV, increased RR, increased RHR across the active pill phases.…”
Section: Discussionmentioning
confidence: 55%
“… 1 28 With resuming exogenous hormone consumption, a stable hormone profile emerges; the inhibitory effects of both the oestrogen and the progestin components are established through synergistic interactions at the hypothalamic–pituitary level. Recently, Assadpour et al 29 suggested the chronic upregulation of β-adrenergic receptors of BC users may play a role in the upregulation of ventilatory rate, and autonomic reflex function, which is reflected in the patterning of the women on BC of this study of decreased HRV, increased RR, increased RHR across the active pill phases.…”
Section: Discussionmentioning
confidence: 55%
“…In addition to differences observed in the blood biomarkers, the ventilatory response to fixed-intensity cycling was different between groups (i.e., ventilation was 2.8 L·min −1 higher in WomenOC compared to WomenNC at Ex 40 ), and the magnitude of difference was dependant on exercise duration. This finding has been noted during some studies (Assadpour et al 2020 ; Quinn et al 2018 ), but not all (Lei et al 2019 ). Since there has been limited research to support OC-induced changes in ventilation, this study provides an important contribution to the literature.…”
Section: Oc and Exercise Physiology (Placebo Trial)supporting
confidence: 53%
“…Since there has been limited research to support OC-induced changes in ventilation, this study provides an important contribution to the literature. A change in ventilatory drive is suggested to occur from the stimulatory effect of (synthetic) progestin on mechanisms relating to respiration, such as increased sensitivity of chemoreceptors (Assadpour et al 2020 ). This is also apparent for (natural) progesterone, whereby ventilation increases during the luteal phase of the menstrual cycle compared to the follicular phase (Dutton et al 1989 ).…”
Section: Oc and Exercise Physiology (Placebo Trial)mentioning
confidence: 99%
“…Therefore, we hypothesize that in the presence of sex hormones in the HH menstrual phase, dCA will be reduced. Since OC users have lower ETCO 2 (Abidi et al, 2017;Assadpour et al, 2020) and no change in the cerebrovascular resistance response (Abidi et al, 2017), we hypothesize that OC users would have enhanced CO 2 reactivity compared to non-users. Lastly, improved dCA has been observed during the second half of pregnancy compared to non-pregnant individuals (i.e., pregnancy sex hormone concentrations are greater than across a menstrual cycle) (Janzarik et al, 2014;van Veen et al, 2016), suggesting that higher levels of sex hormones may have a positive effect on dCA.…”
Section: Introductionmentioning
confidence: 99%
“…Notably, neither Peltonen et al (2016) nor Hazlett and Edgell (2018) included women taking oral contraceptives (OC) and did not concurrently investigate indices of dCA. OC users have been shown to have lower resting levels of end‐tidal CO 2 (ETCO 2 ) (Abidi et al, 2017; Assadpour et al, 2020), which could have an influence on CBF parameters. Additionally, Abidi et al (2017) observed that OC users did not concurrently increase cerebrovascular resistance in response to the observed hypocapnia.…”
Section: Introductionmentioning
confidence: 99%